Exploring gastronomy brands as value-based motivations for cultural and heritage tourism in Nigeria - Nomishan, Terngu Sylvanus; Oloidi, Akintunde John; Aliyu, Bashir (Bahasa Indonesia, 2024)
Gastronomy is the science that studies the connection between foods, traditions, and cultures of different peoples and societies of the world. Gastronomy has always been strongly linked with tourism because when people travel to new areas, they pay great attention to the local culinary habits and traditions. As an intangible cultural heritage (ICH), gastronomy has become one of the primary motivators for tourists’ choices to visit specific destinations. Thus, following this important influence of gastronomy on the tourism industry, there arose a need to study it and uncover some of its salient contributions to tourism development to enhance the transformation of Nigeria’s tourism industry. Therefore, to achieve the aim of this study, the researchers adopted the exploratory research design using key informant interview methods as a data collection tool. Secondary sources were also utilized to enable the drawing of coherent and concise conclusions. The research reveals massive gastronomy or culinary traditions in Nigeria. It is worth noting that these unique cuisines have not received the attention they deserve from all stakeholders, including academics, tourist professionals/practitioners, government organizations, and the general public. As a result, this study is relevant in light of the fact that there is little or no scholarly output on gastronomic tourism in Nigeria.